Criminal evidence - Ingram, Jefferson (John C. Klotter Justice Administration Legal Series, 2012)
"A textbook for individuals teaching or learning about the evidentiary framework in the administration of criminal justice. The materials presented cover general evidence law in use by the states and the federal justice system"--